Stabilizing effect of in-plane angular misalignment in 2DOF sliding system with in-plane anisotropic stiffness. (September 2017) - Kado, Naohiro; Nakano, Ken
Highlights: The yaw angle misalignment (YAM) in sliding systems was focused. The stabilizing effect of the YAM was investigated theoretically in a 2DOF system. Numerical simulation and eigenvalue analysis were conducted. The dimensionless parameters that control the stability were introduced. This method needs no supplementary mechanical devices such as dampers or actuators. Abstract: Recently, it has been theoretically shown that in a 1DOF sliding system, the in-plane angular misalignment (referred to as the yaw angle misalignment (YAM)) has a stabilizing effect to suppress the self-excited vibration induced by the velocity-weakening friction. The YAM theory has been supported qualitatively and quantitatively by some experiments and numerical simulations. However, in some other experiments with another type of apparatuses, the suppression condition was qualitatively different from the theoretical prediction. Based on the above, in this study, the YAM theory has been extended to a 2DOF sliding system with in-plane anisotropic stiffness. Numerical simulation and eigenvalue analysis revealed that the YAM around 45° had a damping effect to suppress the self-excited vibration induced by the velocity-weakening friction, with no supplementary mechanical devices (such as dampers or actuators) to suppress the vibration, which was consistent with the previous experimental results.